Stakeholder cooperation to overcome challenges in orphan medicine development: the example of Duchenne muscular dystrophy. Issue 8 (July 2016) - Straub, Volker; Balabanov, Pavel; Bushby, Kate; Ensini, Monica; Goemans, Nathalie; De Luca, Annamaria; Pereda, Alejandra; Hemmings, Robert; Campion, Giles; Kaye, Edward; Arechavala-Gomeza, Virginia; Goyenvalle, Aurelie; et al.
Summary: Duchenne muscular dystrophy is a rare, progressive, muscle-wasting disease leading to severe disability and premature death. Treatment is currently symptomatic, but several experimental therapies are in development. Implemented care standards, validated outcome measures correlating with clinical benefit, and comprehensive information about the natural history of the disease are essential for regulatory approval of any treatment. However, for Duchenne muscular dystrophy and other rare diseases, these requirements are not always in place when potential therapies enter the clinical trial phase. A cooperative effort of stakeholders in Duchenne muscular dystrophy—including representatives from patients' groups, academia, industry, and regulatory agencies—is aimed at addressing this shortfall by identifying strategies to overcome challenges, developing the tools needed, and collecting relevant data. An open and constructive dialogue among European stakeholders has positively affected development of treatments for Duchenne muscular dystrophy; this approach could serve as a paradigm for development of treatments for rare diseases in general.